Performance of different binders doped Portland Cement-based mortars using volcanic slag, petroleum coke and EPS foam aggregates - Aygormez, Yurdakul (ELSEVIER SCI LTD, 2022)
In this study, besides the control mixture in which only Portland Cement was used, metakaolin (MK) and silica fume (SF) were replaced with Portland Cement by a total of 20% (%10 metakolin + %10 silica fume by weight). In addition to this, different lightweight aggregates were also evaluated instead of natural aggregates. In the specimen where metakaolin and silica fume were used by a total of 20%, volcanic slag (VS), petroleum coke (PC), and expanded polystyrene (EPS) foam were replaced with standard sand by 12.5%, 25%, 37.5%, and 50% (by weight). The 7 and 28 days compressive and flexural strengths of a total of 14 series were examined and voids ratio, unit weight, and water absorption values were found. Also, the freeze-thaw and high-temperature tests were applied to see the behavior of lightweight aggregates and different binders against durability conditions. Scanning Electron Microscopy (SEM) analyzes were applied for the durability tests. The results demonstrated that the compressive and flexural strengths increased by using metakaolin and silica fume together. In addition, strength increases were observed when 12.5% petroleum coke was used and volcanic slag was used up to 25%. 25% volcanic slag improved the mechanical properties, especially by improving the interfacial transition zone (ITZ). In the case of using EPS foam, a continuous decrease was observed. With the results found in this research, it was tried to gain a new perspective in design by using lightweight aggregates in cementitious materials with different binders.
Keywords: Portland Cement; Metakaolin; Silica fume; Volcanic slag; Petroleum coke; EPS foam; High-temperature test; Freeze-thaw test; FLY-ASH; MECHANICAL-PROPERTIES; LIGHTWEIGHT CONCRETE; BEHAVIOR; GEOFOAM; FIBER; HYDRATION; STRENGTH; Construction & Building Technology; Engineering; Materials Science